Electrical faults modeling of the photovoltaic generator, ISSN/ISBN 1974-9821/1974-983X - Rezgui Wail; Mouss Leila Hayet; Mouss Med Djamel (IREMOS International Review on Modelling and Simulations., 2014)
n this paper, we presented a new methodology for the mathematical modeling of the photovoltaic generator’s characteristics based on known electrical laws. This proposed new methodology in this work consists of a three new algorithms, each one presents the characteristic of the cell, group of cells, module, string and generator, when one or more of its components : cells, bypass diodes and blocking diodes subjected to these types of defaults: reversed polarity, open circuit, short circuit or impedance. The three new algorithms obtained can facilitate the prediction for the prognosis or the detection for the diagnosis of these photovoltaic generator’s defaults.